Characterisation of seed germination using nanaobubbled water. Issue 1 (31st December 2022) - Rameshkumar, C.; Lakshmi Sankar, S.; Senthilkumar, G.
Abstract : This paper particularises the generation of nanobubbles in distilled water using electrolysis process. Nanobubbles are those whose diameter is less than 200 nm. The size of the nanobubbles is quantified by using Atomic Force Microscope (A.F.M). This paper also specifies the germination of seeds with nanobubble water for seeds like Tulsi (Holy Basil), beans, surattense night shade and the growth rate is compared with seeds that are germinated with normal water. The comparison is made in terms of number of days the seed took to germinate from the soil, number of days it took for generation of first leaf and number of days it took for perfect branching. It also looks into the case where moss is formed due to over flooding of water for plants. However, mass formation was found to be very less when nanobubbled water was flooded during seed germination. Many property changes are seen in water due to the presence of nanobubbles. So properties like density, viscosity and thermal conductivity of nanobubbles water are studied and the results of these studies hold good harmony with the previous results.